Conversion of injected waste plastics in blast furnace. (2nd January 2016) - Babich, A.; Senk, D.; Knepper, M.; Benkert, S.
Abstract : Operation of several blast furnaces proved that waste plastic (WP) injection makes recycling of industrial and municipal organic wastes and coke saving possible. However, the extent and reaction kinetics of plastic conversion are hardly explored yet. Therefore, a comprehensive study on WP characteristics and conversion behaviour under simulated raceway, bird's nest and shaft conditions, as well as on its interaction with coke, has been undertaken. Numerous analytical, laboratory and pilot facilities have been used. It has shown that despite favourable chemistry, it is hardly possible to reach a high conversion degree of plastics under the raceway conditions. Consumption of unburned residues in coke bed and in shaft is possible. The effect of this phenomenon on coke reactivity has to be considered as well.